FORMATION AND DEVELOPMENT OF CORPORATE CULTURE OF ORGANIZATIONS IN MODERN BUSINESS ENVIRONMENT - VEDERNIKOV, Mykhailo; BAZALIYSKA, Natalia; VOLIANSKA-SAVCHUK, Lesia; VOZNIUK, Ruslan; KLIMAS, Vadim (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article addresses the pressing issues of corporate culture, provides a definition of "corporate culture", and emphasises the importance of corporate culture as a key component of business management. Attention is drawn to the underestimation of the role and importance of corporate culture by domestic business. The main benefits of a strong corporate culture are highlighted. It is noted that corporate culture is related to enterprise management, which includes: type of management, organizational structure, methods of communication and decision-making, employee motivation system, personnel policy and training system. It is noted that the main values of corporate culture are people and information.Corporate culture is determined by the basis of what and how the organization's activities are carried out: what are the values and beliefs that they follow the leadership, which philosophy underlies key policies, which traditions the organization adheres to, the ethical norms that are mandatory for all, and what is the moral situation. Culture thus reflects the atmosphere in the organization and the style of its work. Bearing in mind that corporate culture is just a management tool, it cannot be perfect. In order to be effective, corporate culture has always support the mission, goals and specific strategy of organization development. However, the changes in the corporate culture require a high degree of management competence. In large organizations significant changes in corporate culture usually take from 3 to 5 years. In reality, it is much more difficult to change the existing corporate culture than to create new persuasion in the newly created organization.The formation and development of corporate culture in the modern business environment of the enterprise is analyzed. The interpretation of the essence of the concept of "corporate culture" in the modern business environment of the enterprise is presented. The content of corporate culture in the modern business environment of the enterprise is defined. The primary and secondary mechanisms of corporate culture transfer are characterized. The influence of corporate culture on the management processes of the enterprise's business environment has been established. The influence of the enterprise's corporate culture on target groups (stakeholders) in the business environment is reflected. An analysis of the compliance of the corporate culture with the general strategy of the enterprise was carried out. The relationship between corporate culture and the competitiveness of the enterprise in the modern business environment is shown. A generalized scheme of the influence of corporate culture on the activity of the enterprise in the modern business environment has been built.The article outlines the development of a corporate culture of enterprise in terms of increased competitiveness. The processes of corporate culture and its impact on enterprises in the modern world are deeply analysed.
Keywords: corporate culture; enterprise; business environment; HR; mechanisms of transfer of corporate culture